Older adults and companion animal death: A survey of bereavement and disenfranchised grief - Cary A. Brown; Donna M. Wilson; Eloise Carr; Douglas P. Gross; Maxi Miciak; Jean E. Wallace (Human-Animal Interactions, 2023)
Abstract Background: The number of older adults living with companion animals (pets) is increasing worldwide. While evidence revealing positive relationships between companion animals and healthy aging is well established, there is a dearth of research regarding companion animal death and subsequent human grieving. Some emerging research suggests that grief over companion animal death is often discounted or even unrecognized (disenfranchised) by others. The extent and consequences of disenfranchised grief (DG) are poorly understood. This study deepens our understanding of older adults’ experiences of DG in relation to companion animal death. Methods: Participants from Alberta, Canada, were recruited through social media platforms to participate in an online questionnaire that collected demographic information and standardized measures of companion animal attachment, bereavement, and DG. Results: The majority of the 98 participants were between 60 and 70 years of age, female, and living alone. Following their companion animal’s death, 38.1% identified a decrease in physical activity, and 47% reported that their emotional health had declined. One-third identified that they needed to be careful about who they disclosed their grief, as they were not certain that they would be supported. This group had a significantly greater likelihood of perceived decrease in physical health, and they were more likely to score higher on the Pet Bereavement Questionnaire. Conclusions: This study adds weight to the emergent body of evidence highlighting companion animal bereavement as a legitimate and impactful health and well-being issue. The study found that DG is experienced by a sizable group of older adults following their companion animal’s death and that many participants perceived that socially legitimized recognition of loss and accompanying bereavement resources were lacking. These shortfalls contribute to health risks that negatively affect older adults’ ability to successfully age in the community.